OPTIMALISASI TEKNIK RISET OPERASIONAL UNTUK PENGHEMATAN BIAYA TRANSPORTASI PENGIRIMAN BUAH KELAPA SAWIT DENGAN METODE NORTH WEST CORNER ( STUDI KASUS PT.AGRO MUKO) - Mustadin Mustadin (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2016)
PT.Agro Muko is a plantation company that specifically manages the Palm.In the process of management of oil palm plantations starting up to mills, needed atransport process in the delivery of oil palm fruit. A large number of gardens andobjectives Shipping Oil Palm cause not optimal transportation costs shipping costsCoconut Oil. North West Corner (NWC) is a method to optimize transportation costsby calculating the total costs, the cost of fares and service delivery. NWCimplemented to deal with the cost of shipping oil palm fruit at Muko PT.Agro orderto optimize the transportation cost savings. On the data at Muko PT.Agro CoconutOil shipping costs can be optimized by 3.66% from the current shipping costs. Sothat transportation costs shipping costs Coconut Oil PT.Agro Muko has beenoptimal.